Thalamic Function - Beyond a Simple Relay - William Martin Connelly (Frontiers Research Topics, 2016)
The thalamus is often described as a relay. Typified by sensory pathways, this concept leads to thalamic nuclei being viewed as areas that passively streams information from a single source to the cortex, without affecting the nature of that information. However, diverse intrathalamic connections, the varying synaptic and membrane properties of thalamic neurons and the large number of inputs from non-sensory sources make the idea that the thalamus is just a passive relay unlikely. Furthermore, a large number of thalamic nuclei are not primarily driven by sensory signals nor do they exclusively target the cortex, meaning the thalamus must do more than simply pass sensory signals to the cortex. Finally, there is a wealth of research demonstrating that the thalamus does indeed function in ways that are not captured by the concept of a simple relay. So why, given all of this, is the primary paradigm for describing the thalamus, a relay? This Research Topic covers original research, reviews and hypotheses on thalamic function that explore the concept that the thalamus performs computational tasks other than simply passively relaying information.